2015
DOI: 10.1094/phyto-01-15-0030-fi
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Spread of New Races of Wheat Stem Rust Fungus: Continued Threat to Food Security and Prospects of Genetic Control

Abstract: Race Ug99 (TTKSK) of Puccinia graminis f. sp. tritici, detected in Uganda in 1998, has been recognized as a serious threat to food security because it possesses combined virulence to a large number of resistance genes found in current widely grown wheat (Triticum aestivum) varieties and germplasm, leading to its potential for rapid spread and evolution. Since its initial detection, variants of the Ug99 lineage of stem rust have been discovered in Eastern and Southern African countries, Yemen, Iran, and Egypt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
395
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 390 publications
(403 citation statements)
references
References 77 publications
1
395
0
7
Order By: Relevance
“…However, we clearly demonstrated that stacking QTLs contributed to wide spectrum resistance observed in "Agili39", showing that gene pyramiding is an effective strategy for widening efficacy as evidenced in many other studies (McDonald and Mundt 2016;Singh et al 2017;Singh et al 2014;Singh et al 2011;Singh et al 2015;Singh et al 2005;Singh et al 2016). Albeit that two-way and three-way interactions (chapter 4) not always effectively reduce disease severity -as further demonstrated in our analyses of resistance in contemporary durum cultivars (Chapter 5) -we showed that accumulating the markers for the putative Stb9 allele and 1A-QTL considerably reduced disease in the seedling stage with a dominant effect of the Stb9 over the 1A-QTL.…”
Section: Genetic Makeup Of Durum Wheat Resistance To Stb: the Drasticsupporting
confidence: 70%
“…However, we clearly demonstrated that stacking QTLs contributed to wide spectrum resistance observed in "Agili39", showing that gene pyramiding is an effective strategy for widening efficacy as evidenced in many other studies (McDonald and Mundt 2016;Singh et al 2017;Singh et al 2014;Singh et al 2011;Singh et al 2015;Singh et al 2005;Singh et al 2016). Albeit that two-way and three-way interactions (chapter 4) not always effectively reduce disease severity -as further demonstrated in our analyses of resistance in contemporary durum cultivars (Chapter 5) -we showed that accumulating the markers for the putative Stb9 allele and 1A-QTL considerably reduced disease in the seedling stage with a dominant effect of the Stb9 over the 1A-QTL.…”
Section: Genetic Makeup Of Durum Wheat Resistance To Stb: the Drasticsupporting
confidence: 70%
“…Rusts and mildew have been a major focus of research and breeding because of their ability to overcome deployed race-specific resistance genes in a short time, leading to the phenomenon commonly known as "Boom and Bust" and causing major yield losses. Change in number and spread of detected Ug99 races of stem rust between 1998 and 2015 (92,93).…”
Section: Diseases Caused By Biotrophic Fungimentioning
confidence: 99%
“…the United States from the 1910s to the 1950s; however, SR has been under satisfactory control since 1954 because of the wide adoption of resistant cultivars and the removal of barberry, the alternate host of the SR fungus (93). Epidemics also remained low globally for three decades in the past century except for major epidemics in Ethiopia in 1993 and 1994 on Enkoy, which carries resistance gene Sr36.…”
Section: Diseases Caused By Biotrophic Fungimentioning
confidence: 99%
“…Global demand for wheat continues to increase at an annual rate of 1.6% and certain estimates indicate that 60% more wheat will be needed by the year 2050 (WHEAT, 2014;Singh et al, 2015). Wheat production can be increased either by bringing more area under cultivation or by developing new, high yielding cultivars.…”
Section: Introductionmentioning
confidence: 99%